Pengaruh Kedisiplinan dan Motivasi Kerja Terhadap Produktivitas Kerja Pegawai pada Kantor Badan Kepegawaian dan Pengembangan SDM Kabupaten Maros - Andi Nurfadhilah Azizah; Andi Mustika Amin; Rezky Amalia Hamka; Burhanuddin Burhanuddin; Uhud Darmawan Natsir (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This study aims to analyze the influence of discipline and work motivation on employe productivity at the Maros Regency Personnel and Human Resources Development Office. The method used is quantitative with a descriptive approach. The research sample consisted of 58 respondents, which included all employes at the office, using a saturated sampling technique. Data were analyzed using the SPSS program with multiple linear regression analysis to examine the influence of independent variables on work productivity. The research results indicate that work discipline has a positive and significant influence on employe productivity, with a calculated t-value of 6.848, which is greater than the t-table value of 1.67 and a significance level of 0.000. This means that the higher the employee's discipline, the more their work productivity increases. Work motivation also has a positive and significant effect with a calculated t-value of 7.851 and a significance level of 0.000, indicating that good motivation can drive improved employe performance. Simultaneously, work discipline and motivation have a significant effect on productivity with a calculated F-value of 64.012 > F-table value of 2.40 and a significance level of 0.000. Based on the Beta value, work motivation (0.587) has a more dominant influence than discipline (0.512). However, the coefficient of determination (R Square) value of 0.103 indicates that only 10.3% of the variation in work productivity can be explained by these two variables, while the remaining variation is influenced by other factors such as work environment, competence, and management support. In real-world conditions, even tho employes have good discipline and motivation, external factors also play an important role in increasing productivity. Therefore, human resource management must consider various aspects to improve overall performance.